Matrine in association with FD-2 stimulates F508del-cystic fibrosis transmembrane conductance regulator activity in the presence of corrector VX809 - Marengo, Barbara (Mol Med Rep, 2017)
Cystic fibrosis is caused by mutations of the cystic fibrosis transmembrane conductance regulator (CFTR) gene, and the predominant mutation is termed Phe508del (F508del). Therapy for F508del-CFTR patients is based on the use of Orkambi(®), a combination of VX809 and VX770. However, though Orkambi leads to an improvement in the lung function of patients, a progressive reduction in its efficacy has been observed. In order to overcome this effect, the aim of the present study was to investigate the role of matrine and the in-house compound FD-2 in increasing the action of VX809 and VX770. Fischer rat thyroid cells overexpressing F508del-CFTR were treated with matrine, VX809 (corrector) and/or with a number of potentiators (VX770, FD-1 and FD-2). The results demonstrated that matrine was able to stimulate CFTR activity and, in association with FD-2, increased the functionality of the channel in the presence of VX809. Based on these results, it may be hypothesized that FD-2 may be a novel and more effective potentiator compared with VX770.